Os entraves à adoção da criança e adolescente em acolhimento no NIAC, AIA e Aldeia SOS no município de Mossoró - Soares, Regina Coeli Lopes (Universidade Federal Rural do Semi-Árido, 2019)
Adoption is the insertion of a new member in a family environment, permanently and with acquisition of legal bond. The search for classical adoptions is one of the main obstacles in the adoptive process of children with more advanced age and adolescents. The aim of this study was to analyze the perspectives on the adoption of children and adolescents welcomed by the institutions of the municipality of Mossoró/RN: The institutional welcoming to the Adolescent (AIA), the Integral Child Care Center (NIAC) and the NGO SOS Children's villages, in line with Law Nº 13.509/2017, which modified the statute of the Child and adolescent. This is a qualitative descriptive study that used the technique of content analysis. A semi-structured interview script was applied to the social workers of the aforementioned institutions. In conclusion, it is observed that the relevant legislation, even after important changes, is still not able to effectively decrease the expectation of children and adolescents, especially disabled young people, although the work of the institutions is fundamental importance for the monitoring of those awaiting adoption.
Artigo acadêmico
Keywords: Adoção tardia; Criança; NIAC; SOS Aldeias Infantis; AIA; Late adoption; Child; NIAC; SOS Children's Villages; AIA; CIENCIAS SOCIAIS APLICADAS::DIREITO